Sistem Informasi Reservasi Hotel Rantauprapat Berbasis Web Dengan Framework Codeigniter - Adelia Nitami; Aprilia Andrini Munthe; Masrizal Masrizal (Journal of Student Development Information System (JoSDIS), 2021)
The rapid development of information technology makes many companies, especially in the field of hospitality began to be interested and develop reservation systems using information technology. Rantauprapat Hotel is a one-star hotel located in the center of Rantauprapat located on jl. Ahmad Yani No. 178 Rantauprapat, Labuhan batu, North Sumatra. The process of room reservation at Rantauprapat Hotels is still done in person or by phone, the lack of maximum service delivery to hotel customers due to limitations in obtaining information about hotel room rental in terms of the number of room data, and facilities available.Â  To facilitate the process of room reservation and maximize hotel services to customers, the author built a web-based application program with codeigniter framework that is expected to improve the quality of hotel services Rantauprapat. This hotel reservation information system is built with PHP programming language with codeigniter framework, to help manage MySql database and Notepad++text editor. With the Rantauprapat hotel reservation information system, it can facilitate customers in the process of room reservation, and can provide precise information about empty or already filled room data and available facilities.Â